2022
DOI: 10.3389/fnhum.2022.997230
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for an effect of selective spatial attention on the development of secondary hyperalgesia: A replication study

Abstract: Central sensitization refers to the increased responsiveness of nociceptive neurons in the central nervous system after repeated or sustained peripheral nociceptor activation. It is hypothesized to play a key role in the development of chronic pain. A hallmark of central sensitization is an increased sensitivity to noxious mechanical stimuli extending beyond the injured location, known as secondary hyperalgesia. For its ability to modulate the transmission and the processing of nociceptive inputs, attention co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Although the effect size is small, our findings are in line with studies that have shown that other top-down factors can modulate SH [22,32,45,57,67]. Importantly however, other recent studies that have used similar electrical stimulation protocols, have found either modest or no modulation of SH [4,18,48,65]. This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg.…”
Section: Effects Of Social Support On the Development Of Shsupporting
confidence: 87%
See 1 more Smart Citation
“…Although the effect size is small, our findings are in line with studies that have shown that other top-down factors can modulate SH [22,32,45,57,67]. Importantly however, other recent studies that have used similar electrical stimulation protocols, have found either modest or no modulation of SH [4,18,48,65]. This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg.…”
Section: Effects Of Social Support On the Development Of Shsupporting
confidence: 87%
“…22,32,45,58,68 Importantly however, other recent studies that have used similar electrical stimulation protocols have found either modest or no modulation of SH. 4,18,48,66 This apparent difficulty may be due to the intense nature of the electrical stimulation and the large magnitude of SH that these procedures induce (eg, h p 2 5 0.47 in the current study). In addition, MFS stimulation induces the largest increase in perceived pinprick intensity compared with other frequencies.…”
Section: Effects Of Social Support On the Development Of Secondary Hy...mentioning
confidence: 78%
“…These stimuli elicit pinprick sensations related to the activation of mechanosensitive nociceptors [23,58]. The stimulus was applied following a standardized procedure ( e.g., [12,16]). In line with previous studies (e.g., [12,45,66]) the perceived mechanical sensitivity was assessed three times throughout the whole procedure: before HFS for a baseline assessment (T0), at 20 (T1) and 40 minutes (T2) after the delivery of HFS.…”
Section: Stimuli and Apparatusmentioning
confidence: 99%
“…During the assessment, participants were asked to look away from their arms. Immediately after each stimulus, participants were asked to rate the intensity felt using a numerical scale from 0 (not felt at all) to 100 (maximal pain), with 50 being the transition from a non-painful stimulation to a painful one [16,22,44,45,64]. The same area on the arm was never stimulated more than once.…”
Section: Stimuli and Apparatusmentioning
confidence: 99%
See 1 more Smart Citation